Biological and Medical Sensor Technologies
Biological and Medical Sensor Technologies presents contributions from top experts who explore the development and implementation of sensors for various applications used in medicine and biology. Edited by a pioneer in the area of advanced semiconductor materials, the book is divided into two sections. The first part covers sensors for biological applications. Topics include: Advanced sensing and communication in the biological world DNA-derivative architectures for long-wavelength bio-sensing Label-free silicon photonics Quartz crystal microbalance-based biosensors Lab-on-chip technologies for cell-sensing applications Enzyme biosensors Future directions for breath sensors Solid-state gas sensors for clinical diagnosis The second part of the book deals with sensors for medical applications. This section addresses: Bio-sensing and human behavior measurements Sweat rate wearable sensors Various aspects of medical imaging The future of medical imaging Spatial and spectral resolution aspects of semiconductor detectors in medical imaging CMOS SSPM detectors CdTe detectors and their applications to gamma-ray imaging Positron emission tomography (PET) Composed of contributions from some of the worldÃƒÆ'Ã,Â¢ÃƒÂ¢Ã¢â,¬Å¡Ã,Â¬ÃƒÂ¢Ã¢â,¬Å¾Ã,Â¢s foremost experts in their respective fields, this book covers a wide range of subjects. It explores everything from sensors and communication systems found in nature to the latest advances in manmade sensors. The end result is a useful collection of stimulating insights into the many exciting applications of sensor technologies in everyday life.